ANALYSIS OF STUDENTS'INFORMATION NEEDS IN CONDITIONS OF EPIDEMIC DISTRIBUTION OF CARDIOVASCULAR RISK FACTORS - Tanya Popova; Dimitrina Blagoeva; Nadia Manolova (Peytchinski Publishing, 2022)
Introduction: An epidemic of cardiovascular disease has been observed in Bulgaria for decades. In order to reduce the risk of developing the disease, it is necessary to prevent risk factors, starting in childhood and continuing throughout life. Purpose, material and methods: The aim of the study is to establish students' awareness of risk factors for cardiovascular disease and the nature and need for disease promotion and prevention. Sociological, documentary, statistical methods and method of graphic analysis of the obtained results are used. Results Conclusions: More than 2/3 of study participants know the adjustable risk factors such as alcohol use, smoking, stress and fatigue, and approximately half have information about the negative effects of being overweight and high blood pressure. There is a need for additional information on the impact of other major biological risk factors, such as atherosclerosis, high blood sugar and diabetes mellitus, as well as the impact of unadjustable risk factors - age, gender and family history.